Analisis Tingkat Keramahan Lingkungan Alat Tangkap Purse Seine di Perairan Kota Pasuruan Provinsi Jawa Timur - Lusi Analisa Apriliani; M. Tajuddin Noor; Exist Saraswati (Manfish: Jurnal Ilmiah Perikanan dan Peternakan, 2025)
Pasuruan waters are rich in biodiversity, but are under pressure due to environmentally unfriendly fishing. Purse seine fishing gear is a very productive and efficient fishing gear. This study aims to determine the level of environmental friendliness of purse seine fishing gear. This research will be conducted in the waters of Pasuruan city in November-December 2024. The research method that will be used is the survey method and data will be taken through field observation, interviews and questionnaires. The sample used was 30 respondents. Analysis of the level of environmental friendliness of fishing gear was carried out in accordance with the 9 criteria of the FAO 1995 Code of Conduct for Responsible Fisheries (CCRF). The results of the calculation of the environmental friendliness score, the score obtained was 31.2, which means that the fishing method using purse seine in the waters of Pasuruan City, East Java Province is very environmentally friendly.